Cooling solar panels with bio inspired coconut fiber - Emiliano, Bellini (PV Magazine, 2023)
Researchers at Universiti Malaysia Pahang have developed a novel passive cooling technique for solar modules that uses moist coconut fiber as the cooling agent.